2009
DOI: 10.1111/j.1468-1331.2009.02558.x
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of presence or absence of palmaris longus and fifth flexor digitorum superficialis with carpal tunnel syndrome

Abstract: Our findings showed that the absence of the PL tendon and fifth FDS function, independently and in combination, is more frequent in patients with CTS. Also we found that the severity of CTS or pain distribution in these patients was not related to the presence or absence of these tendons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 18 publications
0
4
0
1
Order By: Relevance
“…After application of the selection criteria to titles and abstracts, a total of 34 articles were identified for detailed examination. Eleven full‐text articles were excluded upon criteria application; one study in Czech language (Dvoráková and Zvolský, ), one study in Polish (Feret et al, ), five studies where dissection was used in assessing PL morphology or presence (Gościcka et al, ; Ito et al, ; Pai et al, ; Stecco et al, ; Albay et al, ), two case reports (Park et al, 2010; Georgiev et al, ), one study reported similar data from another relevant study (Sebastin et al, ), and one comparative study (Saied and Karamoozian, ). The final list comprised 23 relevant articles, with citation tracking and reference scanning revealing a further five for review, of which three were included.…”
Section: Resultsmentioning
confidence: 99%
“…After application of the selection criteria to titles and abstracts, a total of 34 articles were identified for detailed examination. Eleven full‐text articles were excluded upon criteria application; one study in Czech language (Dvoráková and Zvolský, ), one study in Polish (Feret et al, ), five studies where dissection was used in assessing PL morphology or presence (Gościcka et al, ; Ito et al, ; Pai et al, ; Stecco et al, ; Albay et al, ), two case reports (Park et al, 2010; Georgiev et al, ), one study reported similar data from another relevant study (Sebastin et al, ), and one comparative study (Saied and Karamoozian, ). The final list comprised 23 relevant articles, with citation tracking and reference scanning revealing a further five for review, of which three were included.…”
Section: Resultsmentioning
confidence: 99%
“…Although the function of PL is considered very less, but its tendon is reported to be usefulfor reconstructive plastic and hand surgery in tendon graft (Sebastin et al, 2005a), in lip augmentation (Davidson, 1995), ptosis correction (Chauhan, 2003), in management of some facial paralysis (Atiyeh et al, 1998), opponensplasty for severe carpal tunnel syndrome (Park et al, 2010) and excisional arthroplasty for management of keinbock , s disease (Kucuk et al, 2011). Absence of PL may be associated with some morbidities such as carpal tunnel syndrome, wrist compartment syndrome and Guyon's syndrome (Saied and Karamoozian, 2009;Salgado et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Two studies have suggested a probable role for the presence or absence of function in the fifth flexor in the development of CTS (8, 11). One of these concludes that CTS is not related to the presence or absence of the fifth flexor tendon (8), but the other suggested that its absence is a risk factor (11). The sampling method and definition of the absence of the superficial flexor were different in these two studies.…”
Section: Discussionmentioning
confidence: 99%
“…Disputing this finding, at least one study found that presence or absence of the palmaris longus is not a factor in the development of CTS. Similar to palmaris longus tendon, absence of superficial fifth flexor digitorum tendon of the hand is a normal variation (9, 10), and its role has been evaluated as a possible factor in the formation of CTS (8, 11). …”
Section: Introductionmentioning
confidence: 99%